Isokinetic quadriceps and hamstrings muscle strength and the ACL injury in female handball players - Estriga, M.; Carvalho, J.; Bernardes, J.; Massada, L. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
A disproportionate rate of ACL injuries between sexes is frequently reported in high-risk sports involving plant-and-cut movements. The ratio of female risk to male risk is generally between 2 and 3, depending on sport specificity and level of practice. The seriousness of the ACL injury stresses the need to improve the management of its risks and causes. As the knee flexor musculature is important on active knee stabilization, it`s normalized value (hamstrings/quadriceps peak torque ratio - H:Q) has been suggested as an ACL injury risk indicator. Purposes: to characterize the muscular force adaptations over the players` handball career; and to investigate a possible epidemiological correlation between lower limb isokinetic strength and previous or subsequent ACL injuries. Sample: 100 elite Portuguese female handball players, 19±4 years old, practicing handball for 7±4 years. The players were evaluated about 3 months after the beginning of the sport season and any sequent knee injury was registered. They were further subdivided into 3 groups: those with no previous history of ACL injuries (91 players), those with previous or chronic ACL injury (9 players) and those that in the following season suffered an ACL injury (4 players). The isokinetic torque-angle curves were obtained with a Biodex 2 dynamometer at 90º/s (concentric). A clinic evaluation was performed to identify any previous knee injuries and a screening questionnaire was used to assess some vital and sports related information. Results: in players with healthy knees the measured H:Q ratio (45%±7%) is lower than several publish desirable values. In injured players, the knee where reconstructive surgery was performed showed, about 4 years later, approximately 10% reduction of the extension peak torque and no significant reduction on the extension work capability, an indicator of a change in the shape of the torque-angle curve. A small linear neural network (one layer, two node) was trained with half the available isokinetic data. With an optimized turnover point (A=0.981), the model was applied to the full size sample, miss-predicting only 4 cases (4 false-positive ACL ruptures). It even predicted all 4 cases of ACL ruptures that occurred about 1 year after the isokinetic evaluation. A total squared correlation of 62.6% was obtained, with the hamstrings peak torque (36%) as the most powerful single factor. An odds ratio analysis on the logistic regression showed that an improvement of a single N.m on the peak knee flexor torque improves the chance of not having an ACL injury by a factor of 1.27 on average, although the 95% confidence interval contains unity. Conclusions: we could not substantiate the importance of the H:Q isokinetic peak torque ratio as a risk indicator but a more complex model like this may be of some real value. It will improve with all additional evaluations but it already suggests the importance of the knee flexor musculature in the ACL rupture prevention.